2017
DOI: 10.3892/ijmm.2017.3001
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of PCPA against monocrotaline-induced pulmonary arterial hypertension are mediated through the downregulation of NFAT-1 and NF-κB

Abstract: Inflammation and remodeling play a role in the pathogenesis of pulmonary arterial hypertension (PAH). Nuclear factor-κB (NF-κB) and nuclear factor of activated T cells-1 (NFAT-1) participate in inflammation and remodeling in a number of diseases. As a tryptophan hydroxylase inhibitor, 4-chloro-DL-phenylalanine (PCPA) had been reported to exert anti-inflammatory and remodeling effects. Therefore, we hypothesized that PCPA may attenuate monocrotaline (MCT)-induced PAH through the NFAT-1 and NF-κB signaling pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…The canonical NF-κB pathway requires nuclear translocation of a p65/p50 dimer to the nucleus, leading to activation of gene transcription [136]. Activation of this pathway is a key player in vascular and cardiac remodeling, including in PAH and experimental models of severe PH, as shown by our group [94, [137][138][139][140][141][142][143]. Our group has also shown that inhibition of NF-κB reduces occlusive pulmonary arteriopathy in severe PH in rats [141].…”
Section: Central Pathways Driving Inflammationmentioning
confidence: 77%
“…The canonical NF-κB pathway requires nuclear translocation of a p65/p50 dimer to the nucleus, leading to activation of gene transcription [136]. Activation of this pathway is a key player in vascular and cardiac remodeling, including in PAH and experimental models of severe PH, as shown by our group [94, [137][138][139][140][141][142][143]. Our group has also shown that inhibition of NF-κB reduces occlusive pulmonary arteriopathy in severe PH in rats [141].…”
Section: Central Pathways Driving Inflammationmentioning
confidence: 77%
“…The precise action mechanism that leads to PaH remains to be elucidated, but previous studies have indicated that erK and nF-κB signals are closely related to the pathogenesis of PaH (42,43). erK is a main factor of the MaPK family, and its activity in animals with PaH is enhanced (43).…”
Section: Discussionmentioning
confidence: 99%
“…in addition, p-erK is increased in rat lungs exposed to McT, and the suppression of p-erK can prevent the pulmonary vascular remodeling associated with PaH formation (44). notably, erK signaling has been demonstrated to coordinate ecM deposition and inflammatory responses (42,44). The results of the present study were consistent with these previous studies, demonstrating that p-erK was distinctly elevated in the rat lungs exposed to McT, and FMn administration markedly decreased the activated erK induced by McT.…”
Section: Discussionmentioning
confidence: 99%
“…injection of MCT induces vascular remodeling, increases PASMC proliferation and decreases apoptosis by up-regulating anti-apoptotic proteins [ 31 , 32 ]. PCPA, as an inhibitor of 5-HT synthesis, has amelioration effect on remodeling in the PAH [ 31 , 33 ]. But whether PCPA can regulate the apoptosis and its associated signaling pathway is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin plays an important role in PAH. Results from our laboratories showed that the rate-limiting enzyme of serotonin synthesis, TPH1 and SERT expression is increased in PAH [ 31 , 33 ]. Serotonin mediates PAH by inducing pulmonary vascular remodeling and vasoconstriction [ 27 ].…”
Section: Discussionmentioning
confidence: 99%